(3hSjdI GdeJYHOjf Edi eJGHYI SjO GdeQSdjfs - (3eYjf GdOjf CHj MaU YeQ Hf eMeO Hf NVQ GdEQHdj GdehUdj, GdeYQha HGHf GdedGA,J (B570 (3g` s
(3ChdgG (B:s
(3cJGH ai PcQ Ccdg heG Bcdg hTQHg heTGQHg s
(3BNQgG (B:s
(3Qhi Cf GHf SeYhf QVi Gdg Yfg cGf jeTi jhke ai HYV GdWQb aGdJaJ GHf SeYhf Edi LYaQ, hbGd(B: (3jG LYaQ EPG s
(3HYVgG eVHhW HGdTcds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B60s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B471 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs